Subconjunctival haemorrhage: a feature of acute severe asthma. Issue 717 (July 1985) - Rodriguez-Roisin, R.; Torres, A.; Agustí, A. G.; Ussetti, P.; Agustí-Vidal, A.
Abstract : Bilateral subconjunctival haemorrhage was observed on 5 separate occasions in 4 patients presenting a fulminant form of acute severe asthma. Four of these episodes required ventilatory support. All patients recovered from their asthma attack after treatment with bronchodilators, corticosteroids, and oxygen. The incidence of this previously unreported finding represents 5% of the total number of patients with acute severe asthma mechanically ventilated in our intensive care unit from 1976.